1996
DOI: 10.1136/adc.74.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of asthma, rhinitis, and eczema in Singapore schoolchildren.

Abstract: (Arch Dis Child 1996; 74: 131-135)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 23 publications
(10 reference statements)
5
84
1
1
Order By: Relevance
“…Differences in study methodologies may be one of the reasons for these conflicting findings. In contrast to the conflicting findings of whether higher SES increases asthma or wheeze prevalence, the severity level of asthma, asthma mortality, asthma hospitalizations and asthma complications are rather determined by factors associated with poverty [30,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Differences in study methodologies may be one of the reasons for these conflicting findings. In contrast to the conflicting findings of whether higher SES increases asthma or wheeze prevalence, the severity level of asthma, asthma mortality, asthma hospitalizations and asthma complications are rather determined by factors associated with poverty [30,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 79%
“…Living in a rural area might be an indicator for SES. Studies from Africa [37,38], India [39] and Southeast Asia [33] have reported an increase in the prevalence of allergic diseases among children living in or migrating to urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of rhinitis with itchy-watery eyes (ÔrhinoconjunctivitisÕ) over the past year varied across centers from 0.8% to 14.9% in 6-7-year olds and from 1.4% to 39.7% in 13-14-year olds (697,852,883,. The overall correlation between the prevalence of asthma and rhinitis in school children was significant (852,917).…”
Section: The International Study On Asthma and Allergy Inmentioning
confidence: 97%
“…Study by Chhabra et al found no difference in prevalence among socio economic strata whereas study by Goh DY et al found increased prevalence in upper socioeconomic strata. 12,14,13 Majority of children were Vitamin D deficient-80 out of 96 children (83.3%). 3 children (3.1%) had severe Vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%